2014
DOI: 10.1590/0004-282x20140140
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of patients with Alzheimer's disease before and after dental treatment

Abstract: Oral infections may play a role in Alzheimer's disease (AD). Objective: To describe the orofacial pain, dental characteristics and associated factors in patients with Alzheimer's Disease that underwent dental treatment. Method: 29 patients with mild AD diagnosed by a neurologist were included. They fulfilled the Mini Mental State Exam and Pfeffer's questionnaire. A dentist performed a complete evaluation: clinical questionnaire; research diagnostic criteria for temporomandibular disorders; McGill pain question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 24 publications
0
35
0
6
Order By: Relevance
“…The 99 remaining full text articles were then examined for eligibility, of which 62 were then excluded because they did not meet the inclusion criteria. Only one study was added through scanning the reference lists of the included articles [19]. Thereafter, the quality of the 37 included studies was assessed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 99 remaining full text articles were then examined for eligibility, of which 62 were then excluded because they did not meet the inclusion criteria. Only one study was added through scanning the reference lists of the included articles [19]. Thereafter, the quality of the 37 included studies was assessed.…”
Section: Resultsmentioning
confidence: 99%
“…Although dental hard tissues can be an important source of orofacial pain, only seven of the included studies published data about the presence of orofacial pain [15, 19, 28, 33, 34, 44, 74]. The presence of reported dental pain in older people with dementia varied between 7.4 and 21.7 %.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the role of periodontal health for cognitive impairment disease should still be emphasized for the need of functional improvement in the current quality of life of these patients. A study also revealed that periodontal treatment had the effect of reducing co‐morbidities associated with Alzheimer's disease, and routine assessment should be included for these patients (Rolim et al, ). The individuals with cognitive impairment require special attention towards overall oral health care, oral hygiene education, and periodontal maintenance, which may improve daily life activities and life quality (Martande et al, ; Rozas, Sadowsky, & Jeter, ).…”
Section: Discussionmentioning
confidence: 99%
“…A risk factor relationship between periodontal pathogens/periodontal disease and AD exists, as previously discussed by Olsen and Singhrao [3]. Salient points are that periodontal disease is co-morbid with clinically demented subjects [4][5][6][7]. Tooth loss in early and midlife has consequences for poor memory in later life [4,[7][8][9][10][11][12].…”
Section: Making a Case For Periodontitis As A Risk Factor For Alzheimmentioning
confidence: 99%
“…A prospective longitudinal study reported by Ide et al [7] upholds the view that periodontitis is associated with a marked increase in cognitive decline, which is independent of base line cognition, in men with a mild to moderate clinical diagnosis of dementia. A study following the impact of a dental intervention on patients with a clinical diagnosis of mild AD found over 50% of participants (who also suffered from gingivitis/periodontitis) showed improvements in their memory [6]. Oral bacteria and their virulence factors affect the central nervous system pathology [13,14], and indiscriminate release of inflammatory mediators cause neuronal injury [5,[15][16][17].…”
Section: Making a Case For Periodontitis As A Risk Factor For Alzheimmentioning
confidence: 99%